2017
DOI: 10.1111/jth.13674
|View full text |Cite
|
Sign up to set email alerts
|

Comparing thrombin generation in patients with hemophilia A and patients on vitamin K antagonists

Abstract: Essentials It is unknown if hemophilia patients with atrial fibrillation need anticoagulation. Endogenous thrombin potentials (ETP) in hemophilia patients and patients on coumarins were compared. Severe hemophilia patients had comparable ETP to therapeutic international normalized ratio (INR). In non-severe hemophilia, 33% had higher ETP than therapeutic INR and may need anticoagulation. Click to hear Dr Negrier's perspective on global assays for assessing coagulation SUMMARY: Background It is unknown whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 43 publications
(43 reference statements)
3
11
0
Order By: Relevance
“…Finally, it has been demonstrated that the ETP in patients with severe and moderate hemophilia is equal to that of patients on VKAs, whereas mild hemophilia patients are in between controls and VKAs. 16,17 This is in line with our suggestion to withhold anticoagulants in severe hemophilia without prophylaxis but we tend to use them in the very mild cases. As there is considerable heterogeneity within mild hemophilia patients, individualized thrombin generation guided therapy might be the future.…”
Section: Atrial Fibrillation In Hemophiliasupporting
confidence: 73%
“…Finally, it has been demonstrated that the ETP in patients with severe and moderate hemophilia is equal to that of patients on VKAs, whereas mild hemophilia patients are in between controls and VKAs. 16,17 This is in line with our suggestion to withhold anticoagulants in severe hemophilia without prophylaxis but we tend to use them in the very mild cases. As there is considerable heterogeneity within mild hemophilia patients, individualized thrombin generation guided therapy might be the future.…”
Section: Atrial Fibrillation In Hemophiliasupporting
confidence: 73%
“…In the same study, 5 patients with mild haemophilia were analysed, showing more thrombin generation potential than anticoagulated patients but not in the same extend as normal controls. These results were reproduced in a larger study of 133 PWH and 907 patients on VKA (16). These data support the cautiousness of anticoagulant therapy in patient s with severe and moderate haemophilia, but also reflect the ability of thrombin generation in a substantial part of patients with mild haemophilia.…”
Section: Anticoagulation Management In Haemophiliasupporting
confidence: 68%
“…This effect could be related to the metabolism of the compound. Although an enlargement of the clotting time of almost 50% was observed, this does not indicate an effective anticoagulation as it should be in the range of 100–200% enlargement . In fact there is no correlation between the time course of the observed antithrombosis in both arterial and venous model and the effect on clotting ex vivo .…”
Section: Discussionmentioning
confidence: 93%
“…Notably, at the antithrombotic concentration used, LASSBio‐752 did not cause significant bleeding, measured by tail snip, compared with UFH, which was used as the positive control. These findings indicate that LASSBio‐752, in comparison with rivaroxaban, is an effective and safe antithrombotic agent that can be further developed for clinical use in the prevention and treatment of thrombosis or other pathologies associated with deregulated coagulation.…”
Section: Discussionmentioning
confidence: 99%